Addressing the coal conundrum. - Bretz, A.A.
While utopian dreams and advancing technology humankind toward carbon-free energy, today's reality is that fossil fuels drive major economies like China's and India's. Coal, above all, is plentiful and readily available. While everyone's best interests are best served by developing hydrogen-rich and/or carbon-free forms of energy that will emit none (or at least much less) of the gases that cause climate change, those options are not yet fully realized. With this in mind, this paper re-examines the situation in China and India and examines what is being done-and what can be done-to address the current fossil fuel situation
Keywords: China; India; Coal; Coal-fired power; Fossil fuels; Steam power plants